Inventions of Muslim scholars in the field of medicine and the position of hospitals in Islamic civilization - عارف, ا.م.د. زریان سالار حمه‌عارف حمة; أحمد, سمیه‌ عزیز أحمد (Sulaimani Journal for Humanities, 2025)
The subject of hospitals, medical sciences, medicine, and how to treat patients in Islamic civilization until now, and the impact of the progress that occurred at that time on the development of medical sciences today, is of great importance and deserves research and analysis by scientists and scholars interested in the subject, because this issue has been widely talked about since the beginning of civilizations until Islamic civilization, which at that time gave great importance to humans in terms of medicine, treatment, health, and protecting the body in implementation of God’s command, and therefore medical treatment became of great importance to Muslims and Muslim successors, and on the basis of these principles and visions, many efforts were made to movement medical work, so they began to translate medical sciences. And the bringing of doctors and scientists into Islamic civilization, and from here the first hospital and a special place for patients - of various types - was built in Islamic civilization, and many talented doctors appeared and many private medical institutions were established, in addition to that, many hospitals were opened that were in continuous scientific development. And it was constantly discovering new treatments, medicines, and medical equipment for treatment and surgery. This was a surprise and confusion to the Orientalists and other countries, especially European countries and their civilizations that according to Orientalists and explorers , this development and progress did not exist in the history of that time, did not exist and has not been seen, which led to the expansion of... The emergence of Islamic civilization in the medical field took place over several centuries. These reasons and many others, including the modernity and vitality of the topic. We believe that it is necessary to pay more attention to writing in the field of hospitals and Islamic medicine, especially in the Kurdish language, so that the reader becomes more familiar with the scientific progress in the field of medicine in Islamic civilization Islamic studies at that time, and also the novelty of the topic in the Kurdish language, - and this explains the importance of the topic of our research, which is entitled (the inventions of Muslim scholars regarding the characteristics and advantages of hospitals). This is a precise scientific and academic attempt to introduce hospitals, their characteristics and types, treatment methods, innovations of Muslim and non-Muslim doctors in Islamic civilization, and the opinions of orientalists in this regard. Our goal is to shed light on the important aspects of Islamic civilization in the eastern regions in the issues of medicine and Bimaristans and their influence and role in human development and evolution. On the part of human health and safety, the reason for writing this thesis is to answer a number of questions that were the basis for writing this research, such as: Did there be change and development in medicine with the emergence of Islam, and did doctors and medical work have value and appreciation in Islamic civilization? Did Muslim doctors have any innovations in this field? How did the Orientalists view this field in Islamic civilization? The geographical and historical scope of the study deals with doctors and hospitals in the geographical borders of the Islamic East, during the third Abbasid era, between the years (334-656 AH). To write this research, the researcher used the historical and analytical method, and this research achieved Finally, to some important conclusions, which are that Islamic civilization was the beginning and foundation of medical science and medical work, finding medicines and appropriate treatment for patients, and establishing the first hospital through which it was able to play an important role in establishing and developing the science of medicine in European civilization. The structure of the research consists of: an introduction, four chapters, and a conclusion. The list of sources and summaries in Arabic and English is divided as follows: The first section dealt with the inventions of Muslim scholars regarding the characteristics and advantages of hospitals. The second section: It was devoted to the inventions of Muslim doctors in this field.
Keywords: Islamic civilization; Medical treatment in Islam; Islamic pharmacology; Scientific progress in Islamic world